A Corpus-Based Study on Politeness Used by L1 Thai EFL Learners - Pan, Zhaoyi (International Journal of Linguistics, 2022)
This research aimed to identify politeness super-strategies, the strategies under each category of super-strategy, and common lexical patterns in each strategy when performed by L1 Thai intermediate-level EFL learners in English conversation. It attempted to use the corpus-based approach to examine the pattern of how L1 Thai intermediate-level EFL learners use politeness in English conversation and, on the other hand, to examine the existing problems with L1 Thai intermediate-level EFL learners’ use of politeness super-strategies based on the findings. In total, 30 L1 Thai intermediate-level EFL learners were involved in this research. A learner corpus was built to investigate the use of politeness super-strategies and the frequencies of lexical patterns. The findings illustrated that L1 Thai intermediate-level EFL learners tended toward using the negative politeness super-strategy, while no off record super-strategy was found. Moreover, L1 Thai intermediate-level EFL learners used a limited number of politeness strategies under the super-strategy categories identified in this research, with a limited selection of lexical patterns in each strategy. The findings reveal that L1 Thai intermediate-level EFL learners adopt only a small range of politeness strategies, thereby resulting in a discrepancy in the performance of politeness in English conversation.